STRATEGI KESOPANAN YANG DIGUNAKAN OLEH KARAKTER UTAMA DALAM FILM V FOR VENDETTA (Suatu Kajian Pragmatik) - Talolang, Ardiyanto (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT Language has a crucial role in a human life’s communication since it functions as a media tool to make interaction. One way to establish a meaningful conversation in society is by applying politeness. Behaving politely does not merely depend on how good a member in a society is, but also how to behave politely in daily conversation. This study is about politeness strategies used by the main character in